Fluctuations in Learners’ Willingness to Communicate during Communicative Task Performance: Conditions and Tendencies - Mystkowska-Wiertelak, Anna; Pawlak, Mirosław (Research in Language, 2014)
A person’s willingness to communicate (WTC), believed to stem from a combination of proximal and distal variables comprising psychological, linguistic, educational and communicative dimensions of language, appears to be a significant predictor of success in language learning. The ability to communicate is both a means and end of language education, since, on the one hand, being able to express the intended meanings in the target language is generally perceived as the main purpose of any language course and, on the other, linguistic development proceeds in the course of language use. However, MacIntyre (2007, p. 564) observes that some learners, despite extensive study, may never become successful L2 speakers. The inability or unwillingness to sustain contacts with more competent language users may influence the way learners are evaluated in various social contexts. Establishing social networks as a result of frequent communication with target language users is believed to foster linguistic development. WTC, initially considered a stable personality trait and then a result of context-dependent influences, has recently been viewed as a dynamic phenomenon changing its intensity within one communicative event (MacIntyre and Legatto, 2011; MacIntyre et al., 2011). The study whose results are reported here attempts to tap into factors that shape one’s willingness to speak during a communicative task. The measures employed to collect the data – selfratings and surveys – allow looking at the issue from a number of perspectives.